5-n-Butyl-4-[2-(2-ethyl-1-benzothiophen-3-yl)-3,3,4,4,5,5-hexafluorocyclopent-1-en-1-yl]thiophene-2-carbaldehyde - Yang, Zhen (International Union of Crystallography, 2008)
The title compound, C(24)H(20)F(6)OS(2), exhibiting photochromic behaviour, has thienyl and benzothienyl substituents attached to the double-bond C atoms of the envelope-shaped cyclopentene ring. The mean planes of aromatic systems form dihedral angles of 43.0 (1) (thienyl) and 73.8 (1)° (benzothienyl) with the mean plane of the C—C=C—C portion of the cyclopentene ring. This conformation avoids steric hindrance between the n-butyl and ethyl substituents. The formyl substituent of the thienyl group, as well as the ethyl substituent of the benzothienyl group, are disordered [occupancies of 0.788 (17):0.212 (17) and 0.64 (5):0.36 (5), respectively].